Students’ Perception Using YouTube as The Tool to Learn English - Musthafa Fadli Perkasyah Perkasyah; Utami Dewi (Didaktika: Jurnal Kependidikan, 2023)
Lots of apps are created to make all the things easier to be done. For example TikTok, Facebook, You tube, WhatsApp, and another apps . The whole features would get when the user installed on their device. The objective of this research is to know the English students perception in using Youtube as one of the media in learning English. The focus of this research only discuss about YouTubeThe kind of this research is qualitative research with descriptive method. Qualitative research is a research that use to describe the data by explaining it without the number. There are 20 students from English department that choose as the respondent. The instrument of this research is questinnaire. There are 15 statements given on the questionnaire. This research used likert scale to see the respon of respondent. The data is collected by using google form. Researcher share the link to each respondent. The result of this study was most of the students agree Youtubes is better than another apps and the respondent more used Youtube than other apss to study English. Some of the primacy of this app such as; have longer time, various of video, provide paid and unpaid and it is not consumed big data. With these primacy, students’ agree that this app suit to study English.